Pharmacokinetics and safety of fluconazole and micafungin in neonates with systemic candidiasis: a randomized, open‐label clinical trial. (21st June 2018) - Leroux, S.; Jacqz‐Aigrain, E.; Elie, V.; Legrand, F.; Barin‐Le Guellec, C.; Aurich, B.; Biran, V.; Dusang, B.; Goudjil, S.; Coopman, S.; Garcia Sanchez, R.; Zhao, W.; et al.
Abstract : Aims: The pharmacokinetics (PK) of fluconazole and micafungin differ in neonates compared with children and adults. Dosing instructions in product labels appear to be inconsistent with the emerging scientific evidence. Limited information is available on the safety profile of these agents in neonates. Our objective was to study the population PK and safety of both drugs, randomly administered in neonates with suspected or confirmed systemic candidiasis. Methods: Neonates were randomized 1:1 to fluconazole (loading dose 25 mg kg –1 ; maintenance dose 12 mg kg –1 day –1 or 20 mg kg –1 day –1, respectively, for infants <30 weeks or ≥30 weeks' corrected gestational age) or micafungin (loading dose 15 mg kg –1 day –1 ; maintenance dose 10 mg kg –1 day –1 ). PK samples were taken on treatment days 1 and 5. Population parameters were determined using NONMEM and Monte Carlo simulations performed to reach predefined targets. Clinical and laboratory data, and adverse events were collected up to 36 weeks' corrected gestational age or hospital discharge. Results: Thirty‐six neonates were enrolled. The median (range) gestational age was 28.2 (24.1–40.1) and 26.8 (23.5–40.0) weeks for fluconazole and micafungin, respectively. Based on 163 PK samples, the median population clearance (l h –1 kg –1 ) and volume of distribution (l kg –1 ) for fluconazole were: 0.015 [95% confidence interval (CI) 0.008, 0.039] and 0.913, and for micafungin were: 0.020 (95% CI 0.010, 0.023) and 0.354 (95% CI 0.225, 0.482), respectively. The loading dose was well tolerated. No adverse events associated with micafungin or fluconazole were reported. Conclusion: Based on Monte Carlo simulations, a loading dose for fluconazole and dosing higher than recommended for both drugs are required to increase the area under the plasma drug concentration–time curve target attainment rate in neonates.